Confocal fluorescence imaging of photosensitized DNA denaturation in cell nuclei. - Bernas, T; Asem, E; Robinson, J; Cook, P; Dobrucki, J (2005)
The double-stranded helical structure of DNA is maintained in part by hydrogen bonds between strands and by stacking interactions between adjacent purine and pyrimidine bases in one strand. The transition (denaturation) from a double-stranded (ds) to a single-stranded (ss) form can be induced in isolated DNA or fixed cells by exposure to elevated temperatures, alkali or acids, aprotic or nonpolar solvents or some drugs. We report here that DNA denaturation can occur in situ in cell nuclei as a result of interaction between light and an intercalated dye, acridine orange or ethidium bromide. This DNA photodenaturation was probed using metachromatic properties of acridine orange and imaged by fluorescence confocal microscopy. Furthermore, an empirical kinetic model was developed to separate changes of acridine orange luminescence intensities caused by photobleaching from those that were a result of DNA denaturation. We investigated the influence of oxygen on these phenomena and propose a mechanism by which photodenaturation may occur.